Methane Gas Reduction Using Virgin Coconut Oil Supplementation in Rumen Fermentation through in Vitro - Sondakh, Erwin Hubert Barton; Rorong, Johnly Alfreds; Kalele, Jerry Audy Donny (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2015)
This study aims to determine the effect of virgin coconut oil (VCO)supplementation into ruminant feed on the methane reduction in vitro The study used rumen fluid with forage substrate and concentrates in the ratio of 60:40. The experiement consists of five kinds of VCO treatments, namely: R0 â feed substrates without VCO; R1 â feed substrates with 2% VCO; R2 â feed substrates with 4% VCO; R3 â feed substrates with 6% VCO; and R4 â feed substrates with 8% VCO. Each treatment was done three times. The fermentation used Hohenheim Gas TestÂ (HGT) at a temperature of 390Â C for 48 hours. At the end of the fermentation, measurements of methane and microbial activity of the rumen fluid were implemented. Data obtained were analyzed using a completely randomized design, and continued with Duncan test for examining the mean differences. The results showed that methane production descreased by 18.39% - 29.7% when the feed was given 2% - 8% VCO. Based in the findings, it can be concluded that the supplementation of 2% - 8% VCO can be used a substrate for ruminant feed because it can reduce methane and does not interfere the microbial activity of the fermentation of rumen fluid through in vitro.